The influence of gender and income on the household division of financial responsibility - Marcin Hitczenko (Federal Reserve Bank of Boston, 2016)
This paper studies how gender and income dynamics influence the division of responsibility in two-adult households for various activities, including those tasks directly related to financial decisionmaking. The data, from the 2012 Survey of Consumer Payment Choice, consist of the respondents' categorical self-assessments of their individual levels of responsibility for various tasks. A data construct, in which some households have both adults participate in the survey, is exploited to develop a penalized latent variable model that accounts for systemic response errors. The data reveal that that women, even when they are the primary earner, are much more likely than men to have the major responsibility for household shopping and bill paying. With regard to financial decisionmaking, however, there is a greater propensity to share responsibility equally, and income ranking is more important than gender in defining household roles, with higher earners more likely to have a larger share of responsibility.
Keywords: A14; C51; D13; J16; 330; gender roles; household finance; probit models; penalized maximum; likelihood